Interpreting organic spectra - Whittaker, David (Royal Society of Chemistry, 2000)
Spectroscopic data undoubtedly provides a great deal of useful information about organic molecules. Competently deriving structural information from such data therefore, is a requisite skill for many undergraduates studying chemistry. This book covers the basic principles of spectroscopy in as non-mathematical a way as possible. It assumes no previous knowledge of spectroscopy and avoids excessive theory, approaching the topic as an exercise in pattern recognition. Hence the main focus of the book is in the provision of a variety of spectra for the student to interpret. Students are able to pace their progress by gaining confidence on the simpler spectra, and applying techniques learned to tackle more complex examples. As an introduction to the subject, it is ideal for A-level students as well as chemistry undergraduates and will prove to be a very useful reference tool for teachers and lecturers.